2019
DOI: 10.1142/s0218348x19400024
|View full text |Cite
|
Sign up to set email alerts
|

A Geometrical Aperture–width Relationship for Rock Fractures

Abstract: The relationship between fracture aperture (maximum opening; dmax) and fracture width (w) has been the subject of debate over the past several decades. An empirical power law has been commonly applied to relate these two parameters. Its exponent (n) is generally determined by fitting the power-law function to experimental observations measured at various scales. Invoking concepts from fractal geometry we theoretically show, as a firstorder approximation, that the fracture aperture should be a linear function o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…We found β = 0.009, τ = 1.5 and D f = 1.8 to give the minimum RMSE for fractured samples. Note that Ghanbarian et al (2019) found the values of β between 0.1 and 0.001 by fitting their model to experimental data of tensile fractures in the Krafla fissure swarm of northeast Iceland [76]. Besides the 1:1 line (the solid line), the 1:10 and the 10:1 lines are also shown in Figure 8 (the dashed lines).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We found β = 0.009, τ = 1.5 and D f = 1.8 to give the minimum RMSE for fractured samples. Note that Ghanbarian et al (2019) found the values of β between 0.1 and 0.001 by fitting their model to experimental data of tensile fractures in the Krafla fissure swarm of northeast Iceland [76]. Besides the 1:1 line (the solid line), the 1:10 and the 10:1 lines are also shown in Figure 8 (the dashed lines).…”
Section: Resultsmentioning
confidence: 92%
“…where φ is the porosity of porous media and α is the ratio of the minimum width to the maximum width of the fractures (α = w min /w max ). It has been shown that the aperture a (m) is related to the width w (m) of the fracture by the following linear scaling law, e.g., [71,72,75,76]:…”
Section: Geometry Of Fractured Mediamentioning
confidence: 99%
“…We found β = 0.009, τ = 1.5 and D f = 1.8 to give the minimum RMSE for fractured samples. Note that Ghanbarian et al (2019) found the values of β between 0.1 and 0.001 by fitting their model to experimental data of tensile fractures in the Krafla fissure swarm of northeast Iceland [77]. Besides the 1:1 line (the solid line), the 1:10 and the 10:1 lines are also shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…where φ is the porosity of porous media and α is the ratio of the minimum width to the maximum width of the fractures (α = w min /w max ). It has been shown that the aperture a (m) is related to the width w (m) of the fracture by the following linear scaling law [e.g., 72,73,76,77]:…”
Section: Theoretical Development 31 Geometry Of Fractured Mediamentioning
confidence: 99%
“…In many natural and engineering applications, rough channel flows are common. We consider self-affine rough walls, as rough surfaces in nature are often found to be statistically self-affine (Mandelbrot 1983; Kertesz, Horvath & Weber 1993; Ponson, Bonamy & Bouchaud 2006; Ghanbarian, Perfect & Liu 2019). Self-affine surfaces are scale invariant in that the standard deviation of the height difference between two points separated by lateral distance can be expressed as , where is the Hurst exponent that characterizes the surface roughness (Drazer et al.…”
Section: Fluid Flow and Reactive Transport In Channel Flowsmentioning
confidence: 99%